Assessing ecosystem service potentials to evaluate terrestrial, coastal and marine ecosystem types in Northern Germany – An expert-based matrix approach - Müller, Felix; Bicking, Sabine; Ahrendt, Kai; Kinh Bac, Dang; Blindow, Irmgard; Fürst, Christine; Haase, Peter; Kruse, Marion; Kruse, Tim; Ma, Liwei; Perennes, Marie; Ruljevic, Ivana; et al. (Ecological indicators, 2020)
•An updated version of an ecosystem service potential assessment matrix is presented.•The approach combines potentials for 38 ecosystem services in terrstrial, marine and coastal habitats.•Some applications of the matrix are demonstrated for Northern German land- and seascape types.•Uncertainties, potential applicability and future challenges are discussed. In this article, a revised and enlarged version of a qualitative assessment matrix for the appraisal of ecosystem service potentials is introduced. The product is a simple tool for scoring terrestrial, coastal and marine ecosystem types with respect to their abilities to provide provisioning, regulating and cultural ecosystem services as well as indicators of ecosystem state by applying criteria of ecosystem integrity. The methodological steps of matrix development are described, and the emerging expert opinions are illustrated by characterizing different ecosystem types, analysing different ecosystem services and showing the outcomes of linked GIS-based mapping exercises. The applicability of the matrix is demonstrated by some case studies. The related uncertainties are characterized and discussed in context with limitations, arising challenges and conceptual problems. The tool is made available on the internet, and the authors are looking forward to critical checks and proposals for improvement.